An Aggressive Psammomatoid Ossifying Fibroma Presenting as a Sphenoethmoidal Mass - Nwizu, BDS, MMSc, Ngozi N.; George, MD, Mary D.; Chen, MD, PhD, Frank (North American Journal of Medicine and Science, 2010)
Aggressive psammomatoid ossifying fibromas are rare, benign fibro-osseous tumors characterized by the presence of numerous calcified spherules within an actively proliferating connective tissue stroma. They are mainly seen in the sino-naso-orbital region of young individuals. CT scans tend to show a relatively well delineated heterogeneous mass with varying degrees of radiodensity depending on the amount of calcification present. As the name implies, they are prone to aggressive behavior and a high rate of recurrence. We report a case of an aggressive psammomatoid ossifying fibroma presenting as a sphenoethmoidal mass. The relevant histopathological differential diagnoses are also discussed.